Cultural Translation as a Means of Mediating Meaning in EFL Classrooms: A Systematic Literature Review - Nur Alifah Sribudi Wahyuni; Widyastuti; Ali Mustofa (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2026)
This study aims to analyze the role of cultural translation in bridging the gap between linguistic competence and cultural understanding in English as a Foreign Language (EFL) learning. The study employed a systematic literature review design with a qualitative approach, examining 27 articles from 2020 to 2025 obtained from Scopus, Web of Science, and Google Scholar through a screening process based on inclusion and exclusion criteria. Data were analyzed using reflective thematic analysis to identify key thematic patterns in the literature. The synthesis results revealed four main themes: linguistic and cultural gaps in EFL learning; cultural translation as a process of meaning negotiation; the pedagogical implications of cultural translation in EFL learning; and the challenges of its implementation in EFL classrooms. The research findings indicate that EFL learning needs to shift from a linguistically accuracy-based approach toward an interpretive approach that places meaning negotiation and cultural mediation at the core of intercultural communication. This study also repositions cultural translation not merely as a translation strategy or cultural instruction, but as a mechanism of meaning-making in language learning. Furthermore, this study proposes a conceptual model of cultural translation that places cultural interpretation and the negotiation of meaning at the core of EFL learning. Overall, this study demonstrates that cultural translation has the potential to serve as a new pedagogical and conceptual framework to support more reflective, contextual, and relevant EFL learning in the face of the multicultural and digital dynamics of global communication